Optimising Densification Condition of Coffee Husks Briquettes Using Response Surface Methodology - Okello, Collins; Kasisira, Levi Lukoda; Okure, Mackay (Second International Conference on Advances in Engineering and Technology, 2011)
This study was carried out to establish the optimum conditions for converting coffee husks with molasses as binder into a densified biomass fuel. The study was conducted following the response surface methodology (RSM) using rotatable central composite experimental design (CCD). Briquette samples were made by compressing the coffee husks-molasses mixture in a piston and die assembly. The factors in the study were the quantity of binder, die pressure,moisture content, material particle size and dwell time. The density, durability and stability of the densified coffee husks were the response variables. The results of the study indicated that a combination of die pressure of 14.91MPa, moisture content of 8.00% wb, and binder content of 45.00% wb was optimum. Under the optimum settings of the variables, the briquettes produced had a particle density of 718.09 kg/m3 , durability of 80.77% and stability of 14.98%. The study shows that coffee husks can be converted into durable briquettes that can be used to provide the energy required for the development of industry in Uganda.
Keywords: Biomass, Briquettes, Densification, Optimisation